Prevalence of depression and anxiety and associated risk factors among adolescent offenders within the juvenile justice system in Bulawayo and Matabeleland North Province(s), Zimbabwe - Marufu, Marshall Takudzwa (Department of Psychiatry and Mental Health, 2025)
Background The mental health of adolescents is becoming an increasing public health concern. Mental health conditions such as depression and have their onset during childhood. Research has shown that adolescents entering the juvenile justice system are particularly vulnerable to depression and anxiety. Despite the negative consequences associated with these conditions among adolescent offenders, there is a dearth of studies conducted in low and middle countries including Zimbabwe on the prevalence and factors associated with symptoms of depression and anxiety among adolescent offenders between 10-17 years within the juvenile justice system. Thus, the aim of this study is to determine the prevalence and factors associated with symptoms of depression and anxiety among adolescent offenders between 10-17 years within the juvenile justice system in Bulawayo and Matabeleland North Province, Zimbabwe. Methods In total, 130 adolescent offenders aged between 10 and 17 years were recruited in the cross- sectional study using a convenient sampling technique. The Centre for Epidemiological Studies Depression Scale (CES-D-10) and Generalized Anxiety Disorder (GAD-7) were used to measure symptoms of depression and anxiety, respectively. The Alcohol Use Disorders Identification Test (AUDIT), Drug Use Disorders Identification Test (DUDIT), Fagerstrom Test for Nicotine Dependence (FTND), Rosenberg Self-Esteem Scale, and Sexual Risk Behaviour Beliefs and Self-Efficacy Scales were used to measure individual factors associated depression and anxiety. The Juvenile Victimization Questionnaire (JVQ) was used to measure factors associated with mental health conditions at the family level, while the Multidimensional Scale of Perceived Social Support (MSPSS) was used to measure associations at the social level. Means and proportions were used to describe socio- demographic data as well as the prevalence of potential mental health conditions (depression and anxiety). Unadjusted and adjusted associations between individual, family, and social risk factors and the presence of depression and anxiety were also explored. Only those variables that were significant in the unadjusted models were included in the final adjusted regression model. The standard cutoff level for statistical significance used in this analysis is a p-value of 0.05 or less. The findings are presented in the form of odds ratios (ORs) with 95% confidence intervals (CIs). Page | 5 Results The prevalence of depression and anxiety among participants was 18.5% and 10.8% respectively. In total, 7.6% of participants had reported symptoms of both depression and anxiety, highlighting the co-morbidity of mental health conditions among adolescent offenders. After adjusting models, results indicate that adolescents with a known history of mental health problems were more likely to report symptoms of anxiety than those without a known history (OR=15.10, 95% CI 1.86 -122.78). The adjusted models also indicate that adolescents who report more social support are less likely to experience symptoms of anxiety (OR=0.96, 95% CI 0.92 - 0.99). Additionally, the adjusted model shows that participants with high risky sexual behaviour (OR=1.19, 95% CI 1.05-1.35), high self-esteem (OR=1.19, 95% CI 1.05-1.35) and experiencing juvenile victimization or childhood violence (OR=46.87, 95% CI 3.89-565.237) were more likely to have symptoms of depression. Finally, results show that being a first time offender (OR=0.17, 95% CI 0.04-0.80) and having a mother who is alive (OR=0.12, 95% CI 0.02-0.76) are protective factors that reduces the risk of young offenders experiencing symptoms of depression. Conclusion Results from the study show that symptoms of depression and anxiety are prevalent among adolescent offenders within the juvenile justice system and are associated with several risk factors. Selective prevention interventions are recommended for this vulnerable population.